2009
DOI: 10.1007/s00535-009-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of a better outcome of pneumatic dilatation in patients with primary achalasia

Abstract: PD is a safe and effective treatment for achalasia, particularly in older patients who experience a better outcome than younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…In our study, 1 session of PD was clinically effective in 67% of the patients, as Pneumatic balloon dilation in pediatric achalasia Di Nardo et al described in the majority of adult studies reporting an almost 80% success rate, with therapeutic effectiveness similar to that in patients undergoing surgery. 9,[31][32][33][34] Although there are reported perforation rates of 4% to 12% in adult patients, [10][11][12][13][14][15][16][17][18][19][20][21][22] no perforations have been documented in pediatric patients. [23][24][25][26][27][28][29][30] In our series, we did not observe serious complications, only self-limited postprocedural pain in 11% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 1 session of PD was clinically effective in 67% of the patients, as Pneumatic balloon dilation in pediatric achalasia Di Nardo et al described in the majority of adult studies reporting an almost 80% success rate, with therapeutic effectiveness similar to that in patients undergoing surgery. 9,[31][32][33][34] Although there are reported perforation rates of 4% to 12% in adult patients, [10][11][12][13][14][15][16][17][18][19][20][21][22] no perforations have been documented in pediatric patients. [23][24][25][26][27][28][29][30] In our series, we did not observe serious complications, only self-limited postprocedural pain in 11% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several adult studies found that older age, female sex, a long history of symptoms before diagnosis, high pretherapeutic LES pressure, a postdilation LES pressure of less than 10 mm Hg, limited contrast retention on postdilation barium esophagram, and a higher number of repeated baseline PD dilations were associated with a favorable outcome for PD. [11][12][13][14][15][16][17][18][19][20][21][22] All of these studies were performed in adults, and often retrospectively. Experience with pediatric patients is limited to small retrospective series, [23][24][25][26][27][28][29][30] and possible predictive response factors have never been studied in the pediatric age group.…”
mentioning
confidence: 99%
“…Age was thought to be the only factor that determined the response to dilation [4,11,12]. Howard et al [13] reported that a young age at diagnosis and an increased esophageal width on barium swallows predicted a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…PD can result in remission in 67–90% of patients [3]. Tanaka et al [4] reported that old age was the only independent factor that was associated with the success of PD. In addition, Eckardt et al [5] showed that older age and lower post-therapy LES pressures were predictors of good treatment outcomes in patients treated with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from some of the above discussed studies, there are many other studies in literature which concluded old age as a predictor of favorable outcome 27-30. Though, the exact reason for this is not known, there are various hypotheses to explain this finding.…”
Section: Why Is Old Age a Favorable Predictor?mentioning
confidence: 98%